A SURVEY ON BRAIN TUMOR DETECTION AND SEGMENTATION FROM MRI IMAGES - Reshmi, Shruti; Salagar, Rajashekhar D (International Journal of Computer Sciences and Engineering, 2025)
A tumor is a clot or growth of tissues in a brain, which is not normal and causes harm to the tissues. The identification of tumor in brain is a challenging task. MRI (Magnetic resonance image) is a strong radio waves and magnetic field is a type of scan used by MRI to produce diagnosed image of body. The biomedical image processing uses the method of segmentation to explore the useful segmentation. The segmentation method is used to identify the tumor in brain by using different methods such K-mean, Wavelet Statistically Textures Features, Fuzzy C means, Spatial FCM, Proximal Support Vector Machine. This paper gives the overview of the techniques for detection of tumor from MRI images. In this paper, different step are carried firstly preprocessing is used to remove noise from MRI image then Skull of the brain is detect and segmentation method are applied for identification of tumor from MRI image. By using median filter noise are removed from MRI image. The Classification of normal or abnormal brain tumor is carried out by using SVM classifier